Association between albumin corrected anion gap and in-hospital mortality in critically ill patients with chronic obstructive pulmonary disease - Mohan Giri; Anju Puri; Lan Huang; Shuliang Guo (Therapeutic Advances in Respiratory Disease)
Background: The relationship between albumin-corrected anion gap (ACAG) and in-hospital mortality in critically ill patients with COPD remains unclear. Objective: This study investigated the association between ACAG levels and the risk of in-hospital mortality in critically ill patients with COPD. Design: A retrospective cohort study. Methods: This study uses data from the Medical Information Mart for Intensive Care (MIMIC-IV) database. The receiver operating characteristic (ROC) curve was used to determine the optimal threshold for ACAG, and participants were divided into two categories based on this threshold. The primary outcome was in-hospital mortality. We employed univariable and multivariable logistic regression analyses and Kaplan–Meier (KM) survival curves to assess the relationship between ACAG and the risk of in-hospital mortality. Moreover, subgroup analyses were conducted. Results: A total of 2121 patients (54.7% male) were enrolled in the study. The in-hospital mortality rate was 18.9%. In patients with elevated ACAG levels, the in-hospital mortality rate was significantly higher than in those with lower ACAG levels (27.7% vs 11.3%, p  < 0.001). Multivariate logistic regression analysis indicated that even after mitigating for potential confounders, patients in the high ACAG group had significantly greater odds of in-hospital mortality across all models (Model I: OR = 3.000, 95% CI: 2.383–3.777, p  < 0.001; Model II: OR = 3.021, 95% CI: 2.397–3.808, p  < 0.001; Model III: OR = 1.916, 95% CI: 1.458–2.519, p  < 0.001). Patients with elevated ACAG levels have more than twice the risk of in-hospital mortality compared to those with lower levels (hazard ratio (HR): 2.1277, 95% CI: 1.7490–2.5884). Conclusion: This study demonstrates that elevated ACAG levels are strongly associated with an increased risk of in-hospital mortality in critically ill COPD patients, suggesting that ACAG could serve as a potential predictor of adverse outcomes in this patient population.